If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 50x + 75y = 0 Solving 50x + 75y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-75y' to each side of the equation. 50x + 75y + -75y = 0 + -75y Combine like terms: 75y + -75y = 0 50x + 0 = 0 + -75y 50x = 0 + -75y Remove the zero: 50x = -75y Divide each side by '50'. x = -1.5y Simplifying x = -1.5y
| 3(4x+5)+4x+1=96 | | -2.9-4.89=1.75(n+14.5) | | 45n=180 | | 5x-4+3=12 | | 75x^3-192x=0 | | 3(-3x-3)-4x+2=-72 | | 7x-10x=-21 | | 8x=7-x^2 | | 110-11=11 | | 2(6d+3)=18-3 | | 8v-4(v+8)= | | 1(-x+1)+4x-4=-9 | | 110-n=n^2 | | 9n=180 | | 4x+2(5x+4)=162 | | 1(-5x-3)+2x-4=-34 | | 5x+2(7x-17)=61 | | 3(8-b)-39=17b-5(3+4b) | | -10w+10=12w-12 | | -3k+0.3+4.4k-2.1k+4= | | 165=2x+3(7x-14) | | 4x^2-29x-63=0 | | -[15p-1]+24+2[5+5p]=0 | | 3a+20+x=180 | | (73x-58y)-(68x+15y)= | | .07-0.007x=.7 | | 17+13z=17+1 | | (64x+75y)-(-32x+7y)= | | tn=5+(n-1)3 | | 1/4-x=1/2x+9/4 | | (56x+46y)-(2x-7y)= | | y=-x^2+4x+6 |